The Rigveda and the Himalayas: The Influence of Rigvedic Traditions on Spiritual Tourism in Nepal (Rigvedic Himalaya, 2025)
The article, with a focus on the Himalayas as a sacred and revered space, explores the influence of Rigvedic traditions on spiritual tourism in Nepal. The study looks at how these ancient traditions influence the allure of Nepal's spiritual locations, drawing pilgrims and spiritual seekers from all over the world. The paper emphasizes the need of protecting these holy places within the framework of sustainable tourism and cultural preservation. An interdisciplinary approach is used in the study, which combines qualitative research of important spiritual places in Nepal with textual analysis of Rigvedic references to determine their spiritual significance. Finding the best strategies to preserve sacred sites while permitting growth and sustainable tourism is the aim of this study. It has been discovered that Rigvedic hymns honour the Himalayas as a celestial environment, which has strengthened the spiritual ties that Hindu pilgrims have with the region. The study also emphasizes how spiritual tourism, which is motivated by the genuineness of Vedic rituals, has an impact on the economy and culture. Nepal's eco-spiritual tourism projects are in line with the Rigvedas' emphasis on cosmic order (Rta) and harmony with nature.